a PENERAPAN KIMIA FORENSIK: PENGGUNAAN POLONIUM (210PO) SEBAGAI RACUN DILIHAT DARI SEGI TOKSIKOLOGI - Endro Tri Susdarwono (Jurnal Inovasi Pendidikan dan Sains, 2021)
This study intends to provide a description of how the use of polonium-210 (210Po) as a poison in terms of toxicology. This research is a qualitative research, the type of research uses comprehensive analytic studies and analytical normative approaches. Polonium-210 is created in nuclear reactors. This element is very radioactive which if swallowed even a little is very fatal. After entering the blood tissue, the element mainly targets the liver and kidneys and bone marrow. After 210Po is absorbed into the body, the whole body is basically targeted. The dose given and the sensitivity of individual tissues determine the level of damage throughout the body. Unlike most heavy metals, 210 Po accumulates in soft tissue rather than bone. Polonium (210Po) is a producer of very active alpha particles, but only becomes toxic when entering the body. If entered into the human body, toxic effects are often fatal, even at very small doses. Most of the initial dose is quickly excreted in the feces and urine, but the rest is distributed to the soft tissues of the body.